A dual-plane approach for surgical treatment of pseudoaneurysm with arteriovenous fistula in hemodialysis patients - Ji Min Kim; Min Sung Tak; Jin Seok Kang; Chul Moon (Archives of Plastic Surgery, 2021)
Background We report the efficacy of a dual-plane approach using a Dufourmentel skin flap with a purse-string suture of the de-epithelized dermis to manage pseudoaneurysm at the vascular access site for hemodialysis. Methods A retrospective analysis was conducted of 61 patients from 2013 to 2018 with pseudoaneurysms at the arteriovenous fistula or graft who were treated with rhomboid excision, vessel repair with a purse-string suture, and a full-thickness Dufourmentel skin flap. The success rate was defined as the probability of complete wound closure and intact vascular access patency without infection or other complications. Results The success rate was 93.4% at 6 months postoperatively. Complications included newly occurring pseudoaneurysms (n=2), wound dehiscence (n=1) and bleeding (n=1). There were no complications such as stenosis or thrombosis from the procedure. Conclusions A dual-plane approach using a Dufourmentel skin flap with a purse-string suture for vessel repair was shown to be a favorable option for managing stable, small (diameter <2 cm) pseudoaneurysms without infection, rapid expansion, or patency issues of the vascular access.